Low EV/EBITDA multiple : inefficient market or a hidden potential for Fortuna Entertainment Group? - Bochkareva, Ekaterina; Strouhal, Jiří, 1980-; Strnad, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
This thesis was initiated by Penta Investment as a reaction on the significant difference in EV EBITDA multiple of Fortuna and its peers, European listed betting and gaming companies. It seeks to find the reason for more than twice higher multiple and a possibility to increase it by applying best international practices in case there is a feasible way to do it for Fortuna. Three hypotheses address the possible reasons for the difference, peers incomparability, market inefficiency and opportunity for Fortuna to increase the multiple by bringing the most influential KPIs the average level of its peers. The analysis is done with a help of comparative analysis, benchmarking, regression analysis and interviews of equity analysts. As a result, action plan for increasing EV EBITDA multiple for Fortuna is developed.
Vedoucí práce: Jiří Strouhal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses